2007
DOI: 10.1523/jneurosci.2320-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Human Motor Corpus Callosum: Topography, Somatotopy, and Link between Microstructure and Function

Abstract: The corpus callosum (CC) is the principal white matter fiber bundle connecting neocortical areas of the two hemispheres. Although an object of extensive research, important details about the anatomical and functional organization of the human CC are still largely unknown. Here we focused on the callosal motor fibers (CMFs) that connect the primary motor cortices (M1) of the two hemispheres. Topography and somatotopy of CMFs were explored by using a combined functional magnetic resonance imaging/diffusion tenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

48
334
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(387 citation statements)
references
References 65 publications
48
334
4
1
Order By: Relevance
“…Based on the findings of neuroanatomical48 and clinical23, 24 studies, the underlying mechanisms that mediate the effects of Bi‐TENS might include the enhancement of interhemispheric interaction, possibly via the corpus callosum, which is the white matter in the human brain that connects the 2 hemispheres via more than 200 million axonal connections 48. The motor areas of the 2 hemispheres have been shown with functional magnetic resonance imaging and diffusion tensor imaging to be connected via the posterior body of the corpus callosum 48.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of neuroanatomical48 and clinical23, 24 studies, the underlying mechanisms that mediate the effects of Bi‐TENS might include the enhancement of interhemispheric interaction, possibly via the corpus callosum, which is the white matter in the human brain that connects the 2 hemispheres via more than 200 million axonal connections 48. The motor areas of the 2 hemispheres have been shown with functional magnetic resonance imaging and diffusion tensor imaging to be connected via the posterior body of the corpus callosum 48.…”
Section: Discussionmentioning
confidence: 99%
“…Through prior assessment of CMFs in the CC, it is known that CMFs primarily cross through the anterior midbody of the CC, as shown in rhesus monkeys by Pandya et al and Schmahmann et al 11,14) . However, Meyer et al found that CMFs cross through the posterior body and isthmus of the CC utilizing transcranial magnetic stimulation (TMS) measurements, and Hofer et al, Zarei et al, and Wahl et al made the same observations using diffusion tensor imaging (DTI) 2,7,8,13) . In essence, prior studies aiming to obtain accurate anatomical and functional features of the human brain have reported controversial results.…”
Section: Introductionmentioning
confidence: 97%
“…Being the largest fiber bundle, it enables interconnection between the two cerebral hemispheres [1][2][3][4][5][6][7][8] . Previous studies have used magnetic resonance imaging (MRI) to determine several anatomical and morphological attributes of the CC, such as volume, gender difference, and handedness for the evaluation of changes between health and neurological disorders 1,4,6,[9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations